PENGARUH PENGGUNAAN MEDIA SOSIAL DAN KREATIVITAS BERWIRAUSAHA TERHADAP PERTUMBUHAN USAHA PADA BIRO PERJALANAN WISATA CV. KAFA DWIKARYA - Kamila Rasyida Azhari; Keni Kaniawati (Journal of Economic, Bussines and Accounting (COSTING), 2024)
This study aims to analyze the influence of social media usage and entrepreneurial creativity on business success at CV.Kafa Dwikarya, a travel agency. This study uses a quantitative method with a descriptive and associative approach, where data is collected through a questionnaire distributed to 97 respondents who are customers of CV. Kafa Dwikarya. The variables studied are the use of social media (X1), entrepreneurial creativity (X2), and business success (Y). The data collected were analyzed using multiple linear regression to determine how much influence the two independent variables have on the dependent variable. The results showed that the use of social media has a very low influence on business success with a correlation coefficient of r = 0.124. On the other hand, entrepreneurial creativity has a more significant influence with a correlation coefficient of r = 0.416, which indicates a moderate positive relationship. Simultaneously, the use of social media and entrepreneurial creativity have a significant effect on business success with an Fcount value of 11.816 and a significance of 0.000. The coefficient of determination (R2) of 20.1% shows that 20.1% of business success is influenced by the use of social media and entrepreneurial creativity, while 79.9% is influenced by other variables not studied.